Good Corporate Governance: Transparency, Accountability, Responsibility, Independency dan Fairness (Literature Review) - Bambang Karsono (Dinasti International Journal of Management Science, 2023)
Literature Review Articles of Good Corporate Governance (GCG): Transparency, Accountability, Responsiblity, Independency and Fairness is a scientific articles literature review. The purposes of writing this article is to build a hyphotesis of influence or role between variables which will be used in further research, within the scope of Human Resource Management and Leadership. Article Writing Method is library research, sourced by online media such as Google Scholar, Mendeley and other academic online media. The results of this article are: 1) Transparency plays a role in making GCG; 2) Accountability plays a role in realizing GCG; 3) Responsibility plays a role in making GCG; 4) Independency plays a role in making GCG happen; and 5) Fairness plays a role in realizing GCG. Other factors that affect GCG including participatory, inclusive, and follow the rules.